Profile of the teacher of Specialized Educational Service (SES): Professional analysis in a public university in Paraná - Vasquez , Carlos Alberto; Sobral , Rosely Cândida; Machado , Simone Gonçalves; Tureck , Lucia Terezinha Zanato (Seven Editora, 2023)
Specialized educational service (SES) is a right of every person with disabilities, as an integral activity of the inclusive education policy, understood as the set of specific strategies and services that eliminate barriers and enable access to the curriculum, communication and physical spaces considering the specificities of each student, promoting integral education with a view to autonomy and favoring the completion of academic paths in the different levels of education for students with disabilities. Unioeste's Special Education Program (PEE) works to support the entry and permanence of people with disabilities. The objective of this study was to analyze the professional profile of SEA teachers considering the hiring notices. The methodology used is a descriptive research, developed from a case study, with the help of bibliographic and documentary research. The interpretative analysis of the data showed that Unioeste has formalized the attributions of the SEA teacher, that the hiring occurs through simplified selection processes and that the requirements include a bachelor's degree, with a postgraduate degree in Special Education. The results point to the institutionalization of the role of SEA teachers, with compliance with the laws and norms related to inclusive education, but which still lacks support from the State. DOI:https://doi.org/10.56238/sevened2023.008-003